Performan Hasil Silangan Ayam Kampung Jantan dengan Ayam Kedu Betina Pada Fase Produksi Pertama Yang Diberi Ransum Dengan Level Protein Yang Berbeda - Herawati Latif (Jurnal Agripet, 2007)
ABSTRACT. A study on performance of crossed local cock with Kedu hen on production phase given diet with different level of protein have been conducted at experimental farm of Syiah Kuala University. The objective of the research was to study the production performance of local chiken and crossed local cock with Kedu given different level of protein. There were 24 local chiken and 24 crossed local cock and Kedu hen used in trial. The study was designed in Completely Randomized Design (CRD) with factorial pattern 2 x 3 and 4 replications. There were 2 chicks in each replications. First factor was breed of chicken (A); there were local breed of chiken (A1) and crossed breed of chicken (A2). The second factors were the level of protein in the diet e.g. 16% (R1), 18%(R2), and 20%(R3). Parameters studied were feed consumption, hen day production egg weight, feed conversion and egg indext. The data were analyzed by and analysis of variance and as a significant effect was detected, the analysis was breed and crossed breed. However, there were no significant effect on feed consumption, hen day production, egg weight, feed conversion and egg index. Generally, performance of local breed hen which was feed on 20% protein on the diet.